INFLUENCE OF EMULATOR'S NATURE ON DISPERSION AND STABILITY OF ARTIFICIAL LATEX - A. N. Stuzhuk; I. A. Gritskova; P. S. Gorbatov; M. M. Pavlovski; P. S. Zavyazkin (Тонкие химические технологии, 2017)
In this paper, we consider methods for producing artificial latexes based on butadiene-styrene thermoplastic elastomer in the presence of cationic surfactants, as well as their mixtures with nonionic and silicone surfactants. The obtained results are compared for the particle size distribution, and conclusions are drawn about the stability of the polymer suspension. The size of particles of polymer suspensions was determined by the method of photon correlation spectroscopy (dynamic light scattering) using a laser particle analyzer. This method allows us to consider the properties of the resulting polymer suspensions and directly draw conclusions about the effect of nature and the concentration of surface active substances on the stability of the resulting latexes. It can be assumed that in this case, structural- mechanical and electrostatic barriers form in the surface layers of the particles. The combined action of these barriers has made it possible to obtain stable polymer emulsions. Thus, it can be concluded that the used surfactant mixtures make it possible to increase the stability of artificial latexes in the stages of emulsification and distillation.